2017
DOI: 10.1631/jzus.b1600288
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) E6/E7 mRNA detection in cervical exfoliated cells: a potential triage for HPV-positive women

Abstract: Cytology triage has been generally recommended for human papillomavirus (HPV)-positive women, but is highly dependent on well-trained cytologists. The present study was designed to explore whether HPV E6/E7 mRNA detection in cervical exfoliated cells can be a potential triage for HPV-positive women from a clinic-based population. Both the primary HPV testing and Papanicolaou (Pap) test were performed on all eligible HPV-positive women. HPV E6/E7 mRNA was detected by QuantiVirus HPV E6/E7 mRNA assay in cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The figure found that when the optimal cut-off value of HPV E6/E7 mRNA testing is selected at 882.53 copies/ml, the specificity of HPV E6/E7 mRNA testing is improved. Tong-Yu Liu’s and Ye-li Yao’s finding also supported this result [23, 35]. However, the diagnostic performance of HPV E6/E7 mRNA testing was still lower than p16/Ki67 immunocytochemistry.…”
Section: Discussionmentioning
confidence: 63%
“…The figure found that when the optimal cut-off value of HPV E6/E7 mRNA testing is selected at 882.53 copies/ml, the specificity of HPV E6/E7 mRNA testing is improved. Tong-Yu Liu’s and Ye-li Yao’s finding also supported this result [23, 35]. However, the diagnostic performance of HPV E6/E7 mRNA testing was still lower than p16/Ki67 immunocytochemistry.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, a ROC curve was used to further demonstrate the diagnostic performance of HPV E6/E7 mRNA testing, and the optimal cut-off value of mRNA testing is selected at 2097.09 copies/ml. Tong-Yu Liu’s and Ye-li Yao’s finding also supported that when an optimal cut-off value of mRNA testing was found out, the diagnosis accuracy will be improved [20, 29]. As the ROC shows, the AUC of p16/Ki-67 immunocytochemistry is the largest (AUC = 0.799, 95%CI: 0.649–0.908), followed by HPV E6/E7 mRNA testing and HPV DNA assay.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, the sensitivity and specificity of the abovementioned test was estimated at 89.52% and 48.96% respectively in the diagnosis of high-grade squamous intraepithelial lesion of uterine cervix. Additionally, the percentage of positive HR HPV E6/E7 mRNA test results was significantly higher in the histopathological HSIL diagnoses than LSIL [17].…”
Section: Discussionmentioning
confidence: 86%